On the Approximate Controllability of Fractional Evolution Equations with Generalized Riemann-Liouville Fractional Derivative. (18th May 2015) - Mahmudov, N. I.; McKibben, M. A.
Abstract : We discuss the approximate controllability of fractional evolution equations involving generalized Riemann-Liouville fractional derivative. The results are obtained with the help of the theory of fractional calculus, semigroup theory, and the Schauder fixed point theorem under the assumption that the corresponding linear system is approximately controllable. Finally, an example is provided to illustrate the abstract theory.